Anthelmintic activities of the decoction and the hexane-soluble extracts and its fractions from the aerial parts of Cyperus brevifolius Rottb. - Ganot, Shiela Marie S.; Bendoy, Anelyn P. (2014)
In vitro anthelmintic activity of the decoction (CBD) and hexane-soluble extract (CBH) and its fractions of the aerial parts of Cyperus brevifolius ROttb., was investigated against Eudrilus eugeniae earthworms. Crude ethanol extract (CBE) was obtained by soaking the air-dried aerial parts of the plant sample in 95% ethanol followed by filtration. The flitrate was then concentrated utilizing a rotary evaporator, which yielded the hexane-soluble extract (CBH). Five fractions of CBH were obtained by subjecting it through gravity column chromatography. Three concentrations were prepared for CBH and CBD and only 3-mg/mL for the CBH fractions. The results indicated that in terms of mean time of paralysis, CBH has a better anthelmintic activity than CBD at 25-mg/mL concentration as well as at the 50-mg/mL concentration. Furthermore, CBH also gave a better anthelmintic activty compared to CBD at 25-mg/mL concentration and at 50-mg/mL concentration. Among the fractions obtained, only CBH1 and CBH4 showed a notable activity as exhibited by faster mean time of paralysis and death of the test organism compared to its mother solution, CBH. Therefore, C. brevifolius exhibited anthelmintic activity specifically its nonpolar components, the CBH and its fractions.
Keywords: Anthelmintics